Implementation of Screen Time Danger Education to Increase Mothers' Knowledge about Screen Time in Children Aged 2-5 Years - Syahrir, Akifa; Aditya Nihali, Moh Rianto; Apriana, Rista; Agung Ayu , Gusti; Ariani, Putu Putri (Bantayang Omni Cendekia, 2025)
Background: Screen time or digital screen is the time spent by a child or individual using electronic or digital media such as television, smartphones, tablets, or computers, the negative impact of children who use too much screen time that is seen in aspects of language development other than language delays is videos accessed using languages ​​other than those used by people around them, especially English. Objective: To find out the Implementation of screen time danger education to improve mothers' knowledge about screen time in children aged 2-5 years in Bulango Timur Health Center Methods: This design used a descriptive case study method to describe the Implementation of Screen Time Danger Education to improve mothers' knowledge about screen time in children aged 2-5 years in Bulango Timur Health Center. This case study was carried out for one week with three meetings, which guided researchers to assess mothers' knowledge of the dangers of screen time in children aged 2-5 years. Direction were given in the form of questionnaires to the three respondents. Results: The implementation of education about the dangers of screen time on mothers' knowledge in children aged 2-5 years in the seven mother respondents during three meetings a week increased with results in Mrs. W.M as much as 80%, in Mrs. Y.K, Mrs. N.H, and Mrs.S as much as 90% and in Mrs. A.Y and Mrs. W.T as much as 100%. All are in the good category. Conclusion: Based on the results of the case study, it can be concluded that the implementation of screen time education can increase mothers' knowledge about the dangers of screen time in Bulango Timur Health Center.